A randomized, placebo-controlled, cross-over trial of ketamine in Rett syndrome - Kathleen Campbell; Jeffrey L. Neul; David N. Lieberman; Elizabeth Berry-Kravis; Tim A. Benke; Cary Fu; Alan Percy; Bernhard Suter; David Morris; Randall L. Carpenter; Eric D. Marsh; Jana von Hehn (Journal of Neurodevelopmental Disorders)
Abstract Background Preclinical studies and anecdotal case reports support the potential therapeutic benefit of low-dose oral ketamine as a treatment of clinical symptoms in Rett syndrome (RTT); however, no controlled studies have been conducted in RTT to evaluate safety, tolerability and efficacy. Design This was a sequentially initiated, dose-escalating cohort, placebo-controlled, double blind, randomized sequence, cross-over study of oral ketamine in 6–12-year-old girls with RTT to evaluate short-term safety and tolerability and explore efficacy. Methods Participants were randomized to either five days treatment with oral ketamine or matched placebo, followed by a nine-day wash-out period and then crossed-over to the opposite treatment. Ketamine was dosed twice daily at 0.75 mg/kg/dose (Cohort 1) or 1.5 mg/kg/dose (Cohort 2). An independent safety monitoring committee evaluated safety and approved proceeding to the next dose cohort. Caregivers, participants, outcome assessors, and study staff except pharmacists were blinded to allocation. The primary endpoint was safety and tolerability. Exploratory efficacy endpoints included change in clinician- and caregiver-rated measures of RTT features, brain activity on electroencephalography, and wearable biosensors to measure respiration, heart rate, sleep, and activity. Results Twenty-three participants enrolled (11 in Cohort 1, 12 in Cohort 2) from 3/12/2019–11/22/2021. One participant was excluded from analysis due to not meeting inclusion criteria on blinded review prior to analysis. One participant was withdrawn from the study due to an adverse event (vomiting) after the first dose of ketamine. Although planned for four dose cohorts, the trial was stopped after Cohort 2 due to enrollment challenges associated with the COVID-19 pandemic. Ketamine was safe and tolerated in both cohorts, with 1 related treatment emergent adverse event of vomiting. No difference was observed in efficacy between ketamine and placebo. Electroencephalography showed the expected increase in high frequency power with ketamine. Conclusions Short-term, low-dose oral ketamine was safe and well tolerated in girls with RTT. No clinical efficacy of ketamine in treating symptoms of RTT was observed with 5 days of treatment, despite electroencephalography evidence of ketamine target engagement during the first dose. Further studies are needed to evaluate safety and efficacy of higher dose and longer exposure to ketamine in RTT. Trial registration Registered at clinicaltrials.gov NCT03633058.